(untitled) (IDENTITĂȚI VS. DREPTURI. CULEGERE COMENTATĂ DE TEORIE ȘI FILOSOFIE POLITICĂ CONTEMPORANĂ, 2026)
This article explores Charles Taylor’s theory of the politics of recognition and its significance for contemporary debates on identity, equality, and multiculturalism. It argues that individual and collective identities are shaped through processes of mutual recognition and that misrecognition can become a source of exclusion and oppression. By distinguishing between the politics of equal dignity and the politics of difference, the article highlights the challenges of reconciling universal rights with cultural diversity in democratic societies. This abstract is generated with artificial intelligence.